Transvaginal contained tissue extraction after laparoscopic myomectomy: a cohort study. (14th June 2017) - Ghezzi, F; Casarin, J; De Francesco, G; Puggina, P; Uccella, S; Serati, M; Cromi, A
Abstract : Objective: To describe the technique and report perioperative outcomes of transvaginal contained extraction of surgical specimens at laparoscopic myomectomy. Design: Retrospective analysis of prospectively collected data. Setting: Two Italian referral centres for gynaecological minimally invasive surgery. Population: Consecutive patients who underwent laparoscopic myomectomy. Methods: Tissue extraction was accomplished following laparoscopic myomectomy in a specimen retrieval bag via a posterior colpotomy incision. If morcellation was necessary, this was performed extracorporeally, using a scalpel within the specimen retrieval pouch, whose edges were exteriorised through the vaginal introitus. Main outcome measures: Intra‐ and postoperative complications. Results: A total of 316 women underwent transvaginal specimen retrieval with enclosed manual morcellation. The mean myomectomy specimen weight was 154 ± 128 g, and the mean operative time was 79 ± 26 minutes. No intraoperative complications occurred related to the specimen extraction or morcellation technique, or from rupture of the retrieval bag. Two (0.6%) women had a haemoperitoneum that spontaneously resolved and 16 (5.1%) had fever postoperatively. The final pathological diagnosis was benign in all cases. At the 30‐day follow‐up, no pelvic infection, vaginal dehiscence, or complaints of dyspareunia were recorded. Conclusions: Contained transvaginal extraction of fibroid specimens can be performed safely and efficiently in most women undergoing laparoscopic myomectomy. This technique represents a valuable minimally invasive alternative to intracorporeal morcellation. Tweetable abstract: Transvaginal contained morcellation at laparoscopic myomectomy is a valuable alternative to intracorporeal morcellation. Tweetable abstract: Transvaginal contained morcellation at laparoscopic myomectomy is a valuable alternative to intracorporeal morcellation.